The EFFORT OF INCREASING ORGANIC RICE PRODUCTION BASED ON FIELD SCHOOL OF ORGANIC FARMING - Hasanah, Yaya (Talenta Publisher Universitas Sumatera Utara, 2019)
People's preference for switching to a healthy lifestyle by buying organic food has increased the demand for organic rice. The problem that arises is the gap between organic rice production and consumption. The solution to the problem that can be done in increasing organic rice production is through the Field School of Organic Farming (FS-OF). This FS-OF activity is aimed to increase farmers' understanding of organic rice cultivation through learning and training in organic rice cultivation. Implementation of activities in FS-OF was conducting training, and direct learning in the form of demonstration plots. The service activities that have been carried out include the production of demonstration plots for organic and conventional rice cultivation to compare their production, handover of technology transfer tools, training in organic rice cultivation, making the liquid organic fertilizers and organic pesticides, and biochar. Keywords : rice, organic, field school, farming